THE QUALITY OF PUBLIC SERVICES IN THE PURWANEGARA VILLAGE OFFICE, NORTH PURWOKERTO SUB-DISTRICT, BANYUMAS REGENCY - Ganesa Eka Suswanti; Andri Trianfano; Oti Kusumaningsih (DYNAMICS: Journal of Public Administration, 2023)
This research is entitled "Quality of Public Services in Purwanegara Village, North Purwokerto District, Banyumas Regency". The aim is to analyze and describe the problem of the quality of public services in Purwanegara Village. The research method uses a qualitative descriptive method whose informants are selected by purposive sampling techniques. This study used observational data collection techniques, interviews and documentation. The data analysis method uses an Interactive Analysis Model.Based on the results of research conducted in Purwanegara Village, North Purwokerto District, Banyumas Regency, it can be concluded based on 5 aspects as follows:Tangibility (physical evidence) of facilities and infrastructure in Purwanegara Village is good with seating for people waiting for service queues, in the service room there is air conditioning and there are service brochures along with the requirements of all services. Two, The reability of the ability of Purwanegara Village officers to provide services accurately, reliable in administration and skilled in using tools or facilities to support services, and have clear service procedures. Three, Responsiveness (responsiveness) of service delivery officers has carried out services quickly, precisely and responsively but there are still obstacles, especially when the officers are not in place (absent / wide service). Four, Assurance (guarantee) guarantee of punctuality in Purwanegara Village is good, but there are still services that are hampered due to having to use online applications and waiting for data updates from the center which causes people to wait 1-2 days. Finally, Emphaty (empathy) the attitude of officers / officers in friendly, polite service and helping people who feel difficult.